Complementary feeding practices among infants and young children in Abu Dhabi, United Arab Emirates - Zainab Taha; Malin Garemo; Joy Nanda (BMC, 2020)
Abstract Background Optimal complementary feeding (CF) promotes health and supports growth and development in children. While suboptimal feeding practices are reported for many countries, very limited information exists about such practices in the United Arab Emirates (UAE). The present study describes CF practices in Abu Dhabi, UAE, and evaluates them using the United Nations Children's Fund (UNICEF) Programming Guide: Infant and Young Child Feeding. Methods In this cross-sectional study, participating mothers of children below the age of two reported on their children's CF introduction and practices via a structured questionnaire. The study received ethical approval (ZU17_006_F) from Zayed University. Results Out of 1822 participating mothers, 938 had initiated complementary feeding for their children, who had a mean age of 7.1 ± 5.9 months. Three quarters of the children (72.2%) were introduced to CF in a timely manner between the ages of 6 and 9 months. A majority (71.4%) consumed ≥4 food groups, i.e. the recommended minimum diet diversity. In total, less than half (47.3%) of the children met the requirements for minimum meal frequency, with the non-breastfed, 6-23 month old children being the least compliant (21.9%) (p < 0.001). Many children were fed with sugar-containing snack items. Overall, 36.2% of the children aged ≥6 months had a minimum acceptable diet. Conclusion The gap between the suboptimal CF practices and the recommendations may be attributable to poor knowledge about feeding practices rather than food availability problems. Effective intervention programs can facilitate improvements in the feeding practices to better support a healthy upbringing among Abu Dhabi infants and toddlers.